Inclusive Economic Development in Indonesia: An Empirical Study of Local Government Contribution - Muhtar, Muhtar (Accounting Study Program, Faculty Economics and Business, Universitas Sebelas Maret, 2023)
This research attempts to present empirical evidence of the determinants of inclusive economic development in Indonesia, specifically from local government contribution. We use secondary data from the related government institutions in Indonesia in 2019, analyzed with multiple regression. Our analysis figures out that the local governments have reached a satisfactory level of inclusive economic development although the West Indonesian region still delivers better achievement than the East Indonesian region. Moreover, the empirical analysis demonstrates an insignificant effect on local government economic function development and local wealth that indicates the need for improvement. Meanwhile, the supervision conducted by the local government exhibits a positive effect on inclusive economic development that emphasizes the importance of the government's role in safeguarding public interest in the pursuit of local development improvement. The study provides several practical implications for local governments to increase their role in supporting inclusive economic development. First, the spending quality in local government must be improved from planning to realization. Local governments should also need to optimize the local wealth with optimum asset utilization to realize its potential benefit. Finally, adequate supervision must be maintained both in procedural and financial aspects in every program implementation so that inclusive economic development all over Indonesia. Penelitian ini berupaya memperoleh bukti empiris terkait determinan pembangunan ekonomi inklusif di Indonesia, khususnya dari kontribusi pemerintah daerah. Peneliti menggunakan data sekunder dari instansi pemerintah terkait di Indonesia pada tahun 2019 yang dianalisis dengan regresi linier berganda. Analisis kami menunjukkan bahwa pemerintah daerah telah mencapai tingkat pembangunan ekonomi inklusif yang cukup memuaskan meskipun wilayah Indonesia Barat masih memiliki pencapaian yang lebih baik daripada wilayah Indonesia Timur. Selain itu, analisis empiris menunjukkan pengaruh yang tidak signifikan dari belanja fungsi ekonomi pemerintah daerah dan kekayaan daerah yang mengindikasikan perlunya perbaikan. Sementara itu, pengawasan yang dilakukan oleh pemerintah daerah berdampak positif terhadap pembangunan ekonomi inklusif yang menekankan pentingnya peran pemerintah dalam menjaga kepentingan masyarakat dalam upaya peningkatan pembangunan daerah. Studi ini memberikan beberapa implikasi praktis bagi pemerintah daerah untuk meningkatkan peran mereka dalam mendukung pembangunan ekonomi inklusif. Pertama, kualitas belanja pemerintah daerah harus ditingkatkan dari perencanaan hingga realisasinya. Pemerintah daerah juga perlu mengoptimalkan kekayaan daerah dengan pemanfaatan aset secara optimal untuk merealisasikan potensi manfaat aset. Terakhir, pengawasan yang memadai harus dilakukan baik secara prosedural maupun finansial dalam setiap pelaksanaan program agar pembangunan ekonomi inklusif di seluruh Indonesia.